Pengaruh Model Cooperative Integrated Reading And Composition (CIRC) Terhadap Kemampuan Berkolaborasi Pada Mata Pelajaran Bahasa Indonesia Kelas II SDN Maospati 3 (Eduscotech, 2022)
The problem in this research is the low ability of students to collaborate in class II SDN Maospati 3.. The purpose of this study is to determine the significant effect on the application of the Cooperative Integrated Reading and Composition (CIRC) model. This method of research is quantitative research. The research design used is a non-equivalent control group design. This study used a saturated sample technique with a total of 34 students. The instruments used are test and non- test instruments. The results of testing the hypothesis obtained significant value data < ttable (5% significance level, α = 0.05) with details of 0.02 < 0.05, then Ha is accepted and Ho is rejected. The results of this study indicate that there is a significant influence of the Cooperative Integrated Reading and Composition (CIRC) model on the ability to collaborate in class II Indonesian language subjects at SDN Maospati 3.